Proceedings 2006 IEEE International Conference on Robotics and Automation, 2006. ICRA 2006.
DOI: 10.1109/robot.2006.1641793
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian estimation for autonomous object manipulation based on tactile sensors

Abstract: Abstract-We consider the problem of autonomously estimating position and orientation of an object from tactile data. When initial uncertainty is high, estimation of all six parameters precisely is computationally expensive. We propose an efficient Bayesian approach that is able to estimate all six parameters in both unimodal and multimodal scenarios. The approach is termed Scaling Series sampling as it estimates the solution region by samples. It performs the search using a series of successive refinements, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 8 publications
0
75
0
Order By: Relevance
“…Force-sensitive fingers have been used to control the robot's position [6], i.e., to continuously keep the finger in physical contact while moving the object. It has also been shown that tactile sensors can be used to estimate the 3D pose of objects with known shapes [16]. Notably, little information is recovered from the tactile sensor in this work, resulting in multimodal distributions due to ambiguities during the first grasps, which is a problem we are also dealing with in our work.…”
Section: Related Workmentioning
confidence: 94%
“…Force-sensitive fingers have been used to control the robot's position [6], i.e., to continuously keep the finger in physical contact while moving the object. It has also been shown that tactile sensors can be used to estimate the 3D pose of objects with known shapes [16]. Notably, little information is recovered from the tactile sensor in this work, resulting in multimodal distributions due to ambiguities during the first grasps, which is a problem we are also dealing with in our work.…”
Section: Related Workmentioning
confidence: 94%
“…To improve performance, we turn to Scaling Series, a method first proposed in Petrovskaya et al (2006) for a tactile localization application. In that application the number of parameters was also too large to perform an importance sampling step in real time in conditions of global uncertainty.…”
Section: Scaling Seriesmentioning
confidence: 99%
“…They proposed the Scaling Series algorithm to efficiently produce a much more informed proposal distribution, one that is concentrated around the areas of high probability mass. We refer the reader to Petrovskaya et al (2006) for details on Scaling Series, but briefly, the algorithm works by performing a series of successive refinements, generating an increasingly informative proposal distribution at each step of the series. The successive refinements are performed by gradually annealing the measurement model from artificially relaxed to realistic.…”
Section: Scaling Seriesmentioning
confidence: 99%
“…However, for highly accurate sensors, even such an adaptive technique might require a huge number of samples in order to achieve a sufficiently high particle density during global localization. Alternatively, one can artificially inflate the measurement uncertainty to achieve a regularization of the likelihood function, e.g., see the Scaling Series approach presented by Petrovskaya et al [11]. Also Kalman filters have limitations in highly non-linear systems and in the case of multi-modal likelihood functions.…”
Section: Related Workmentioning
confidence: 99%